Knowledge and self-reported practices on the discarded disposable masks during the COVID-19 pandemic: a case study in Perak - Mohd Yusoff, Mohamad Arief Hafizi (2023)
The use of facemasks is mandatory to prevent the spread of the COVID-19 virus. Inadequate waste treatment creates substantial hazards of disease transmission to waste pickers, waste workers, health workers, patients, and the population at large. This study aims to assess knowledge and practices on discarded disposable masks (DMs) during the COVID-19 pandemic. The study area was conducted in Perak. A crosssectional online survey of 385 Perak residents was conducted. The survey instrument consisted of demographic characteristics, 19 items on knowledge, and 18 items on practices, adopted from a previously published questionnaire. Pearson correlation analysis and Multiple Linear Regression were used to assess the association between the participants' demographic features and knowledge and practises, using a two-tailed test for survey findings. Self-reported knowledge revealed that 348 individuals, or 90.38% and have a good level of knowledge regarding the disposal of DMs while practices of the participants show mean rating of 1.95±0.70 which is moderate practices. There were significant associations between gender and types of residence (p<0.05) with knowledge. For practices showing gender and education level are significantly correlated which is (p<0.05). Regression analysis for knowledge and practices in disposing DMs on the demographic show that gender and types of residence are significant to knowledge which is (p<0.05) while gender and education level is significant to practices which is (p<0.05). As a conclusion, taking precautions to notify as many individuals as possible is important in promoting the behaviour of the public to wear a mask. Social media is the most effective way to interact with the public. In addition, enforcement actions also need to be improved to educate and teach the public about the importance of proper disposable mask disposal.